Heterogeneous Expectations and Bond Markets - Xiong, Wei; Yan, Hongjun (Review of Financial Studies, 2010)
This paper presents a dynamic equilibrium model of bond markets in which two groups of agents hold heterogeneous expectations about future economic conditions. The heterogeneous expectations cause agents to take on speculative positions against each other and therefore generate endogenous relative wealth fluctuation. The relative wealth fluctuation amplifies asset price volatility and contributes to the time variation in bond premia. Our model shows that a modest amount of heterogeneous expectations can help explain several puzzling phenomena, including the “excessive volatility” of bond yields, the failure of the expectations hypothesis, and the ability of a tent-shaped linear combination of forward rates to predict bond returns.